KARAKTERISTIK PARAMETER SPESIFIK DAN NON SPESIFIK DAUN KRATOM (Mitragyna speciosa Korh.) ASAL KALIMANTAN SELATAN - Febrianti, Dwi Rizki; Wahyuono, Subagus; Fakhrudin, Nanang; Riski, Akhmad; Kumalasari, Eka; Normilawati; Niah, Rakhmadhan; Mar'uf, Muhammad (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Standardization is a process of fulfilling the requirements for raw materials of traditional medicine, aimed at ensuring and maintaining safety, consistent quality, and efficacy. Kratom leaves (Mitragyna speciosa) are a traditional medicinal plant found in the interior regions of Kalimantan. This plant functions as a source of energy due to its stimulant properties. This study aims to determine the standardization of kratom leaf extract simplicia, including both specific and non-specific parameters. The extraction method used in this study was maceration with ethanol. The results showed that the scientific name of kratom leaves is Mitragyna speciosa. The standardization of kratom leaf simplicia powder includes parameters such as loss on drying, total ash, water-insoluble ash, acid-insoluble ash, total microbial count (ALT), total yeast and mold count (AKK), and heavy metal contamination, with the following results: 9.5%; 5.51%; 3.58%; 0.39%; 6.9 × 10² cfu/g; >3.0 × 10³ cfu/g; <0.001 mg/kg. Meanwhile, the standardization of kratom leaf extract includes ash content and heavy metal contamination, with results of 6.06% and <0.001 mg/kg, respectively. The active compounds contained in the kratom leaf simplicia and extract are alkaloids, flavonoids, and tannins.